The impact of Al-Azhar University on Arabic-Islamic schools in Yorubaland, Southwestern Nigeria - Abdus Salam, Yunus Olatoke (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2014)
This study aims to examine the impact of Al-Azhar University in Cairo, the Arab Republic of Egypt, on Arabic-Islamic schools in the Yorubaland, Nigeria. This is done through investigation of its curriculum, and of Al-Azhar's delegates teaching in Arabic-Islamic schools in Yorubaland, Nigeria. It discusses Islamic religious affairs and the role played by the Nigerian Muslim scholars in general and in the South Western Nigeria in particular. Furthermore, it addresses the arguments on the need to pursue religious education within and outside the country. This study also examines the differences between Al-Azhar and the Nigerian Arabic- Islamic educational systems and investigates the need for continuation or otherwise of Al-Azhar's venture in the Nigerian Arabic- Islamic Schools. This study is both historical and analytical in nature. It used data gathered via primary and secondary sources such as books, interviewing some scholars in Nigeria, and distribution of questionnaire to Nigerian students in Egypt. Findings from this study revealed the suitability of Al-Azhar educational system for Nigeria. It also showed the continuous need to pursue Al-Azhar education by Nigerians. There was also emphasis on introducing some Western courses into Al-Azhar educational curriculum. The study recommends the completion of secondary education in Nigeria by intending Nigerians seeking Al-Azhar education in Egypt in order to facilitate their usefulness in the Nigerian western-oriented educational system upon their return.